Ứng dụng hàm nhậy loga đánh giá dự trữ ổn định các hệ điều khiển một vòng với thông số biến đổi theo thời gian - Châu, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
This paper expresses a possibility for estimating the stability margin of the feed-back control system composing a plant with slowly time-varying parameters and a PI or PID controller. The motivation of this approach is the use of a logarithmical sensitivity defined in the time domain and permited to fulfill the real-time requirement.